Persepsi Wisatawan Lokal pada Interior Onshore Floating Resort - Nastiti, Ratna Andriani; Ayuswantana, Alfian Candra; Tanadda, Onna Anieko; Fata, Ibrahim; Herwina, Nevlin Cresentia; Dini, Mazaya Islami (Program Studi Desain Interior Unikom, 2024)
The concept of healing has gained significant popularity in Indonesia, particularly in light of the recent surge in Covid-19 cases. The term